A 16-Year Climatology of Polar Stratospheric Clouds Based on CALIPSO Measurements (2006–2021) and Relationship with the Stratospheric Temperatures - Konstantinos Koutsougiannis; Michalis Stamatis; Stergios Misios; Nikos Hatzianastassiou (Environmental Sciences Proceedings, 2023)
A 16-year global climatology of polar stratospheric clouds (PSCs) for the period 2006–2021 is produced, using satellite data products from the CALIOP lidar. The original Level 2 data (at 5 km horizontal and 180 m vertical resolution, from 8.5 to 30 km) were re-gridded at 1° × 1° latitude-longitude, for 121 vertical layers, on a monthly basis. From the obtained statistics the areal coverage and fractional cloud cover of PSCs were estimated. According to our analysis, PSCs are found in altitudes ranging from 13 to 25 km above the Earth’s surface, with the maximum frequency between 18 and 22 km, peaking in July in the Southern Hemisphere, and mostly in January in the Northern. Results show that the areal extent of PSCs, at the altitude of maximum frequency of occurrence, has increased over the NH from 2006 to 2021, and decreased over the SH, but these trends are not statistically significant. Stratospheric temperatures seem to follow a similar temporal and spatial pattern as that of PSCs.